2010
DOI: 10.1111/j.1651-2227.2010.01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal blood glucose concentrations in caesarean and vaginally delivered term infants

Abstract: Background: Little is known about the glucose concentrations at and after birth of infants delivered by caesarean section (CS), when compared with infants born vaginally (VD).Aim: To compare venous cord blood glucose concentrations of term infants born after elective CS to infants born by VD. We studied the null hypothesis that mode of delivery does not affect neonatal blood glucose values. Methods:We compared cord blood glucose concentrations in healthy term infants born after VD (n = 16) or by elective CS (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 8 publications
3
25
0
1
Order By: Relevance
“…There are many fetal and perinatal complications of cesarean delivery e.g. obesity, allergies, metabolic disturbance, and lower blood glucose levels in the offspring [3-6]. …”
Section: Letter To the Editormentioning
confidence: 99%
“…There are many fetal and perinatal complications of cesarean delivery e.g. obesity, allergies, metabolic disturbance, and lower blood glucose levels in the offspring [3-6]. …”
Section: Letter To the Editormentioning
confidence: 99%
“…The implication of these studies is that fetal AMCs are capable of responding to hypoglycemia with inappropriately timed catecholamine secretion. On the other hand, the transport of wastes and nutrients across the umbilical cord is of necessity occluded at birth, and blood glucose decreases to a nadir of about 2-3 mM during the first 2 h of life before stabilizing at a higher level (26,30,39,51,54). Tissue concentrations of glucose are likely to be much lower at this time given that, during hypoglycemia, interstitial glucose can decrease to ϳ34% of plasma glucose (37).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, fetuses are completely dependent on their mothers for the transplacental facilitated diffusion of glucose. During normal birth, this transport ceases, leading to a decrease in blood glucose (hypoglycemia) in the first few hours of life (26,30,39,51,54). In the newborn, hypoglycemia activates a counterregulatory surge in catecholamines and glucagon and a fall in insulin (11).…”
mentioning
confidence: 99%
“…However, in 2010, Marom R et al reported that the glucose concentrations in infants who were born by vaginal deliveries were higher than in the infants who were born by elective caesarean sections without labour; but no scientific explanation was provided [11].…”
Section: Discussionmentioning
confidence: 99%